Safety And Effectiveness Of Supraglottic Airway Devices In Cesarean Sections Under General Anesthesia: A Systematic Literature Review - Patricia Mamuraja; Made Suandika; Adiratna Sekar Siwi (International Journal of Health Engineering and Technology, 2026)
Airway management during cesarean section (CS) under general anesthesia carries risks of complications such as aspiration, hypoxemia, and hemodynamic responses resulting from airway manipulation. Second-generation supraglottic airway devices (SADs), such as the LMA Supreme, have been developed as an alternative to endotracheal tubes (ETTs). The purpose of this study is to evaluate the safety and efficacy of second-generation SAD compared to ETT in SC under general anesthesia. This study employed a Systematic Literature Review (SLR) method in accordance with the PRISMA 2020 guidelines. The literature search was conducted in the PubMed, ScienceDirect, and Google Scholar databases, covering the years 2015–2025. The included studies comprised Randomized Controlled Trials (RCTs), cohort studies, and retrospective studies evaluating the use of SAD in SC. Quality assessment was performed using the Joanna Briggs Institute (JBI) instrument. A total of 8 studies met the inclusion criteria. The results showed that second-generation SADs had high insertion success rates, adequate ventilation, and maternal and neonatal outcomes comparable to those of ETT. No significant increase in aspiration, hypoxemia, or airway complications was observed. Supraglottic Airway Devices (SADs) demonstrated more stable hemodynamic responses and faster insertion times. Second-generation supraglottic airway devices (SADs) are an effective and relatively safe alternative to endotracheal intubation (ETI) in selected patients undergoing cesarean section under general anesthesia. Evidence regarding high-risk populations, particularly those with hypertension during pregnancy, remains limited.